345 Elective Anterior Cervical Discectomy and Fusion vs Cervical Artificial Disc Replacement: A Comparison of Perioperative Morbidity and Early Outcomes. (1st August 2016) - Upadhyayula, Pavan S.; Yue, John K.; Hoshide, Reid; Curtis, Erik; Ciacci, Joseph D.
Abstract: INTRODUCTION: We conducted a retrospective cohort analysis of early outcomes after elective anterior cervical discectomy and fusion (ACDF) vs cervical artificial disc replacement (C-ADR) using the National Surgical Quality Improvement Program database. Risk factors associated with operation time, hospital length of stay, early complications, and discharge destination were studied. METHODS: Adult patients undergoing elective ACDF or C-ADR were abstracted from American College of Surgeons National Surgical Quality Improvement Program years 2011 to 2014. Univariate analyses were performed by surgery cohort for each outcome, and corrected for demographic/clinical variables (age = 65, sex, race, body mass index (BMI), ASA score, functional status, inpatient/outpatient status, smoking, hypertension, Charlson Comorbidity Index) using multivariable regression. Means, standard errors, odds ratio (OR), and 95% confidence intervals (CIs) are reported. Significance was assessed at P < .05. RESULTS: Of 18 067 subjects (ACDF = 17 296, C-ADR = 771), C-ADR subjects were on average younger (<65 years: 97.4% vs 84.2%; P < .001), less obese (nonobese: 6.10% vs 49.1%; P < .001), less physically burdened (ASA 1: 13.1% vs 4.3%; ASA 3-4: 17.9% vs 38.3%; P < .001), less functionally dependent (0.5% vs 2.2%; P < .001), and presented with fewer overall comorbidities (3.9% vs 6.4%; P < .001). Overall, 31 (0.17%) patients died. Univariate analyses showed that C-ADR had shorter operation time (111.27 ± 1.89-minutes vs 125.59 ± 0.53-minutes; P < .001), shorter hospital length of stay (HLOS) (1.06 ± 0.03 days vs 1.64 ± 0.04 days; P = .003), and higher likelihood of being discharged to home (99.5% vs 96.9%, P < .001). Multivariable analysis confirmed C-ADR association with shorter operation time (B = −9.37; 95% CI, −14.34 to −4.01) and with greater likelihood of returning home (OR, 2.74 [1.01, 7.41]), while a nonsignificant statistical trend was demonstrated for HLOS (B = −0.35; 95% CI, −0.73 to 0.03). Incidences of early complications did not differ between C-ADR and ACDF (1.4% vs 2.5%, P = .620). CONCLUSION: Patients selected for elective C-ADR demonstrate lower comorbidity profiles than ACDF. Compared with ACDF, C-ADR is associated with decreased operative times and increased likelihood of being discharged home. Future studies are needed to confirm these findings.